The use of ketotifen as long-term anti-inflammatory prophylaxis in children with PFAPA syndrome - Kapustova, Lenka; Banovcin, Peter; Bobcakova, Anna; Jurkova Malicherova, Eva; Kapustova, Daniela; Petrovicova, Otilia; Slenker, Branislav; Markocsy, Adam; Oleksak, Filip; Vorcakova, Karolina; Jesenak, Milos (Frontiers in Immunology, 2023)
Periodic fever, aphthous stomatitis, pharyngitis and adenitis syndrome (PFAPA) is the most frequent periodic fever syndrome in children. Its pathogenesis is still unknown, but some disease-modifying factors were observed. Several medications were tested for the long-term prophylaxis of inflammatory flares; however, none are standardly used. This prospective clinical trial enrolled 142 children (71 girls, 50%) meeting diagnostic criteria for PFAPA syndrome. We analysed selected clinical characteristics and compared laboratory parameters during the flare and attack-free period (at least two weeks after the attack). Moreover, we assessed the possible therapeutic effect of ketotifen on the duration of attack free-periods and clinical picture. The mean age of patients was 6.81±3.03 years and the mean age of onset of symptoms was 2.31±2.02 years. No significant differences were observedbetween genders.We recorded a positive family history for PFAPA in 31.69% of patients. Attacks lasted for 2.8±1.2 days, with intervals between attacks of 4±1 weeks. We administered ketotifen in 111 (77.8%) patients, and a positive effect was observed in 86 (77.5%) of patients. We observed prolonged attack-free intervals in patients treated with ketotifen (14.7±8.9 days in comparison with 4.4 ±1.9 days before the treatment; p<0.001). The used dose of ketotifen was 0.08±0.01 mg/kg/day. Mild side effects were observed in fourpatients (restlessness, irritability, agitation and constipation).Our data supports the use of ketotifen for long-term prophylaxis in children with PFAPA syndrome with positive effects on the attenuation of disease activity and the prolongation of attack-free periods. Further well-designed studies should confirm thepreliminary data.